Energy dependence of polarized 𝛾⁢𝛾→𝑒+⁢𝑒− in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at RHIC - STAR Collaboration (Physical Review C, 2025)
We report the differential yields at mid-rapidity of the Breit-Wheeler process (𝛾⁢𝛾→𝑒+⁢𝑒−) in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC), as a function of energy √𝑠𝑁⁢𝑁, 𝑒+⁢𝑒− transverse momentum 𝑝T, 𝑝2T, invariant mass 𝑀𝑒⁢𝑒, and azimuthal angle. In the invariant mass range of 0.4<𝑀𝑒⁢𝑒<2.6GeV/𝑐2 at low transverse momentum (𝑝T<0.15GeV/𝑐), the yields increase while the pair √⟨𝑝2T⟩ decreases with increasing √𝑠𝑁⁢𝑁, a feature that is correctly predicted by the QED calculation. The energy dependencies of the measured quantities are sensitive to the nuclear form factor, infrared divergence and photon polarization. The data are compiled and used to extract the charge radius of the Au nucleus.
Keywords: Computer science; dept.phy; peer-reviewed